Liposomal‐Encapsulated Near‐Infrared Fluorophore Based on π‐Extended Dipolar Naphthalene Platform and Its Imaging Applications in Human Cancer Cells. (10th December 2020) - Jung, Yuna; Kim, Byeong Wook; Jung, Junyang; Kim, B. Moon; Kim, Dokyoung
Abstract : A new near‐infrared emitting liposomal nano‐formulation was developed, which has a dipolar dye in the core and demonstrated for human cancer cells' fluorescence imaging.